Ukrainian and Russian phraseology arising during the COVID-19 pandemic - Khoroz, Nataliya (Slavia Centralis, 2021)
The spread of COVID-19 worldwide has caused certain processes in almost every language. In particular, in the Ukrainian and Russian language, there is a phenomenon of adapting well-known fixed phrases to extra-lingual conditions through their various transformations. It is the transformed fixed phrases thematically related to the topic of the coronavirus that have become the subject matter of this article. They have been systematised: a) considering the types of transformations applied to them; b) considering the influence of transformations on the semantics of fixed phrases; c) considering the subject. These fixed phrases constitute the latest occasional phraseological picture of the Ukrainian and Russian world. Their fixation and study are important for understanding speech processes in synchrony, in their relationship to the extra-lingual situation.
Keywords: covid-19; phraseological unit (PU); transformation; occasionalism; semantics; ideographic analysis